Navigating Writing Challenges: A Study on High-Use Learning Strategies Among Successful EFL Learners in Indonesia - Rezky Fakhir Hilmi; Yenni Rozimela (STAI Hubbulwathan Duri, 2025)
Writing in a foreign language presents challenges related to grammar, vocabulary, coherence, and self-regulation. This study investigates the writing learning strategies employed by successful EFL learners in the English Education Study Program at Universitas Negeri Padang. The objective is to identify the most frequently used strategies to overcome these difficulties. A quantitative descriptive approach was employed, utilizing a survey questionnaire to collect data from a purposive sample of 30 successful EFL learners. The questionnaire assessed the frequency of various writing strategies, categorized into metacognitive, cognitive, compensation, social, memory, and affective strategies. Findings indicate that all strategy types fall under the